PENGARUH EDUKASI TENTANG MENSTRUASI TERHADAP SELF EFFICACY SISWI DALAM MENGHADAPI MENARCHE DI SD NEGERI 1 SELOMUKTI - Wulandari, Inaya (Nurul Jadid University, Probolinggo, East Java, Indonesia, 2024)
Menarche is a phase of physiological changes experienced by all young women involving changes in the hormonal system which are characterized by physical, biological, psychological, cognitive and emotional changes in the body where this phase is a transitional phase from childhood to adulthood. (Permatasari, 2021). The purpose of this study was to analyze the effect of education about menstruation on the self-efficacy of female students in dealing with menarche at SDN 1 Selomukti Situbondo. The research method used Quasi Experiment using a pretest-posttest design and the sampling technique used in this research was a total sampling of 35 respondents. Data analysis in this study used the paired T-test. The result Showed that there is an effect of education about menstruation on the self-efficacy of female students in dealing with menarche at SDN 1 Selomukti Situbondo with Asymp.Sig 0.000 < α = 0.05 Ha is accepted. Thus it can be concluded that there is a significant difference between before and after being given menarche education. There is an influence of education about menstruation on the self-efficacy of female students in dealing with menarche at SDN 1 Selomukti Situbondo.